Risk Assessment of Irrigation-Related Soil Salinization and Sodification in Mediterranean Areas - Tomaz, Alexandra (2020)
Salinization and sodification are important processes of soil degradation a ecting irrigated lands. A large proportion of the global irrigated area is a ected by some degree of soil salinity or sodicity caused by the intensification of irrigation. The increase of the frequency of adverse climatic conditions, like high temperatures and variations in precipitation patterns caused by climate change, will potentially amplify these processes in arid, semi-arid, and Mediterranean areas. The use of integrated approaches for the spatial and temporal prediction of the risk of salinization and sodification in irrigated areas is of great value, helping in the decision-making regarding land uses and choice of more suitable agricultural practices. In this study, based on key criteria for the assessment of irrigation-related salinization processes (e.g., climate, topography, soil drainage, water quality for irrigation, and crop irrigation method), we developed a methodology for the prediction of soil salinity and sodicity risk in irrigated lands, using two composite indices, the Salinization Risk (RSA) index and the Sodification Risk (RSO) index. The application of these indices to a real scenario (a Mediterranean area in Southern Portugal) showed that 67% of the potentially irrigated area presented a low risk of salinity development, 68% had a moderate risk of sodification, and 16% was of high risk of sodicity development. Areas under moderate risk of salinization (26%) were mostly characterized by low slopes and fine-textured soils, like Luvisols and Vertisols, with limited drainage conditions. Areas with high risk of soil sodification presented a large incidence of low slope terrain, moderate-to-restricted soil drainage, in high clay content Luvisols, Vertisols and Cambisols, and land use dominated by annual crops irrigated with surface or sprinkler systems. These risk prediction tools have the potential to be used for resource use planning by policymakers and on-farm management decision by farmers, contributing to the sustainability of irrigated agriculture in Mediterranean regions.